Tandem cervical carotid stenting for stenosis with flow diversion embolisation for the treatment of intracranial aneurysms. Issue 1 (17th December 2018) - Campos, Jessica K; Lin, Li-Mei; Beaty, Narlin B; Bender, Matthew T; Jiang, Bowen; Zarrin, David A; Coon, Alexander L
Abstract : Background: An estimated 2%–3% of the population harbour an intracranial aneurysm. Concomitant atherosclerotic cervical carotid disease is not uncommon. The management of these two entities remains a challenge within the field. Case presentation: We report a single case of concomitant carotid stenosis and two ipsilateral unruptured intracranial aneurysms treated with a single-staged cervical carotid stenting and cerebral aneurysm embolisation with the Pipeline embolisation device. Discussion: No consensus currently exists to guide endovascular treatment of intracranial aneurysms associated with asymptomatic ipsilateral stenosis. Here, we present a case of asymptomatic moderate carotid stenosis with two ipsilateral intracranial aneurysms and suggest carotid artery stenting takes procedural priority over aneurysm embolisation in single-stage treatment. The rationale for the sequence of neurointerventions is based on the tracking a robust distal access system beyond a stenotic proximal carotid lesion and stabilisation of the ulcerated plaque to avoid thromboembolic complications associated with plaque irritation during aneurysm embolisation. Additional cases and longer follow-up will be needed to further assess the efficacy of this technique.